KEPATUHAN KONSUMSI TABLET TAMBAH DARAH PADA REMAJA PUTRI - Anita Widiastuti; Rusmini Rusmini (POLTEKKES KEMENKES SEMARANG, 2019)
The healthy generation is passed down from the previous healthy generation. For that we need good preparation so that when a pregnant woman is in optimal healthy condition. Healthy conditions will give birth to a healthy generation. Long before becoming pregnant, young women must be prepared to have good health habits. The purpose of this study was to determine compliance with the consumption of added blood tablets in adolescent girls between urban and regional areas. This type of research is descriptive which illustrates adherence of young women in consuming blood- added tablets. The population / research subjects in this study were young women who were targeted by the Fe supplementation delivery program. Schoolgirls have received an added blood packet. In its development there are students who are obedient and there are students who are less obedient in consuming Fe supplementation. For schools in the regions, the consumption of blood added tablets 100% of respondents spend the added blood tablets that have been received. While for students who are in urban areas who spend less than 50% add blood tablets. The conclusion that there are still many cases of anemia in schoolgirls who are taking the program added to the tablet added blood. This can be attributed to the awareness that is still lacking in consuming blood-added tablets. It is recommended for schools to be able to help make students aware of consuming blood added tablets that have been given from the government.